Ás sete nós criamos a outra: imagens de controle e as adolescentes mães e gestantes sob custódia do Estado. - Melo, Luísa Azevedo de (2022)
In this work, we analyze the persistent violation of the rights of adolescent mothers or pregnant women in state custody because they are named as in conflict with the law. This question arose in the context of the granting of collective Habeas Corpus 143.641/SP by the Federal Supreme Court in 2018, in which it aimed to ensure the freedom of all women subjected to precautionary detention in the national penitentiary system, whether they were pregnant, postpartum or mother. of children up to 12 years of age under your responsibility. The general objective of this research was to identify the images of control operating on adolescent mothers and pregnant women deprived of their liberty. It started from the hypothesis that control images are being articulated to deny adolescents the usufruct of rights guaranteed for more than three decades and reaffirmed throughout legal proceedings, such as HC 143.641. The epistemological contribution of this research was outlined by the thinking of three intellectuals who share an anti-essentialist, humanizing and committed political-epistemological stance with the creation of spaces for the subaltern’s speech: González (2020), Spivak (2010) and Collins (2019). The research was divided into four parts. First, we use the analytical keys provided by Spivak (2010) to think about modern rationality and Law through the notions of sovereign and subaltern subject. In the second chapter, through the lens of Amefricanity, we intertwine the analytical categories formulated by Collins (2019), especially the category of control images, with the analyzes of Gonzalez (2020) that seek to understand the racist and sexist dynamics ideologically operating in Brazil. In the last chapter, we analyzed the traces of control images involving HC 143.641. Going through the political context of deferral to the legal (in)consequences of extending the benefit to pregnant adolescents or mothers in state custody. We analyzed what the absence of data from the magistrate's speech says about the subalternity relationship of these adolescents in relation to the Brazilian justice system. If in Brazil racism operates through denial, the concealment and silencing of these teenagers says a lot about the blunders of Brazilian legal conscience.